Designing High Availability Cluster Using Server Virtualization on Cloud Storage Services - Ali Idrus (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Cloud Storage Service at PT. Harrisma Globaltechnologies Jakarta has not been applied based on virtualization. The problem with cloud storage services in general is that the server is not able to serve a high number of requests as a result the cloud storage server fails. One of these problems is caused by inadequate server resources and less than optimal storage server management. These problems can be solved effectively and efficiently with server virtualization. Where server virtualization is managed by Proxmox. Proxmox is an open-source virtualization platform supported by KVM and OpenVZ hypervisors and can be managed with web-based graphics. Server virtualization collaboration can save server resources by duplicating server services virtually. The research methodology used is clustering by applying the concept of high-availability where there is a secondary server as a backup-server for the primary-server. The results of this study include three parameters, namely Throughput, Response Time, and CPU Usage. The results show that cloud storage servers that implement virtualization than those that do not apply with a difference in the value of the Throughput parameter of 1896.6 Kbps, the difference in the value of the Response Time parameter of 10.6 requests/second, and the difference in the value of the CPU Usage criteria of 11.91%